Exploring Teacher Assessment Literacy in Practice within the Implementation of Kurikulum Merdeka: A Case Study of EFL Teachers in Temanggung Regency - Lestari, Wahyu Puji; Astuti, Puji (Universitas Negeri Semarang, 2025)
Many teachers still find difficulties in practicing the paradigm of Kurikulum Merdeka, specifically regarding assessment. Several studies have identified the relationships between teachers’ assessment literacy and their practices. However, investigation into those two fields according to the Kurikulum Merdeka are still scarce. Therefore, this study attempts to explore the EFL teachers’ assessment literacy in practice regarding the implementation of the Kurikulum Merdeka, as well as the challenges and institutional support for teachers. The study employs qualitative design in form of exploratory case study basing on Xu and Brown’s (2016) model framework of teacher assessment literacy in practice (TALiP). Three teachers and principals were involved as the main participants. This study found mixed findings for each aspect of TALiP and there was connection between teachers’ conceptions, knowledge, and practices of assessment. Teachers were found to have implemented the assessment as instructed in the Kurikulum Merdeka, although not yet optimal. Furthermore, contextual factors affecting the practices were mainly in form of external factors, such as time constraint, excessive workload, and diverse students. Therefore, schools have attempted to provide supports by promoting professional development program, optimizing school community of practice, developing communication and collaboration, building reflection culture, and increasing teacher as well as student motivation. The findings of this study are expected to provide inputs for educational stakeholders in order to find solutions for better implementation of the Kurikulum Merdeka, especially in the language assessment field in a larger context.